Pengaruh Penerapan Self Efficacy Terhadap Motivasi Belajar Siswa Kelas III SD - Junaidi, Junaidi; Salwa, Nada; Zulfiana, Siti; Anwar, Faizi (Arfah BHMS Foundation, 2025)
Learning motivation is an internal drive that encourages students to learn and achieve their academic goals. However, many students still experience low learning motivation, which affects their academic performance. Factors such as environment, family, socio-economics, learning methods, and student characteristics influence learning motivation. Low learning motivation has a broad impact on students. The academic impacts include decreased learning achievement, poor grades, difficulty understanding the material, lack of interest in learning, and the risk of dropping out. The psychological impacts include low self-confidence, difficulty making decisions, stress, anxiety, and negative thinking patterns. This study aims to determine the effect of self-efficacy on student learning motivation. Sampling was conducted using the cluster sampling technique. The sample size used in this study was one class, namely class III, with 21 students. The method used was a quantitative method with a regression approach. Data on students' self-efficacy and learning motivation were collected through questionnaires. The data obtained were then analyzed using simple linear regression tests assisted by IBM SPSS Statistics 25. The results of this study indicate that self-efficacy has a significant effect on the learning motivation of third-grade students at SD Negeri 3 Mamben Daya, with a T-value of 4.246 greater than T-table (1.729) at a significance level of 0.000. Keywords: influence, self-efficacy, learning motivation